GASTRONOMIC TOURISM AND ITS CONTRIBUTION TO THE REGIONAL TOURISM MARKET - Vafoxodjayeva Dilafruz Rahmatulloevna (American Journals, 2024)
There is a chance to support the local economy, sociocultural, and environmental preservation through gastronomy tourism. The purpose of this study was to look at the gastronomy tourist industry in touristic regions and how it contributes to the regional tourism market. The potential phenomena in Uzbekistan's gastronomic tourism development, particularly in tourist areas, is the reason this topic was selected. Triangulation data collecting was used in conjunction with qualitative methodologies to conduct the study. with the assistance of the local administration, the food sector, tourists interested in gastronomy, and the community. The results were produced using the ANOVA data analysis approach and the flow model analysis technique.
Keywords: Gastronomic tourism, tourism contribution, touristic region, gastronomic tourist, regional tourism, tourism market.